Morbidity and Mortality Associated With Respiratory Virus Infections in Allogeneic Hematopoietic Cell Transplant: Too Little Defense or Harmful Immunity? - Versluys, Anne Birgitta; Boelens, Jaap Jan (Frontiers in Microbiology, 2018)
The impact on morbidity and mortality of Community Acquired Respiratory Virus (CARV) infections in patients undergoing Allogeneic Hematopoietic Cell Transplant (HCT) is widely studied. Here we give an overview of the current literature on the incidence and chance of progression to severe disease in this highly immunecompromised population. We discuss the issue whether it is predominantly direct viral damage that causes clinical deterioration, or that it is in fact the allogeneic immuneresponse to the virus that is most important. This is an important question as it will guide therapeutic decission making. It asks for further collaborative studies focussing on sensitive surveillance with PCR techniques and relating clinical data with parameters of immunereconstitution.